AB1413 PHA-BRIC: Therapeutic information of rheumatology patients receiving biologics in cochin hospital. (23rd January 2014) - Natella, P.A.; Hesbert, A.; Nivina, A.; Dahan, E.; Seynave, V.; Bouscarrut, E.; Gossec, L.; Roux, C.; Dougados, M.; Flipon, E.
Abstract : Background: The service of Rheumatology offers patients a daily hospital unit to receive Biologic treatments such as infliximab, abatacept, rituximab or tocilizumab. Other patients coming to the consultation receive prescriptions for Biologics used on an ambulatory basis. EULAR recommendations suggest the need of information and education [1]. Pha-BRIC is a two part study containing a satisfaction assessment of pharmacist intervention and an observation of knowledge evolution of patients through pharmacist action. Objectives: Therapeutic information of these patients was initiated at the clinic in order to explain the treatment, the possible common side effects and provide other valuable information. The quality of such initiative was then assessed. Methods: Informational cards with practical hints (leaflets) were developed by a team consisting of a pharmacist, pharmacy students and rheumatologists. The header of each 2-page leaflet had the name of the Biologic medicine, its international non-proprietary name and therapeutic class. Other sections were: form and conservation; beneficial action; administration; most common side effects; efficiency estimation; other important information concerning the medicine. Leaflets were given, before or during the infusion, by a pharmacy student and explained according to patients previous knowledge and questions. Afterwards, a questionnaire evaluating the need of therapeutic information was filled in by the patient. Inclusion started in May 2011 and finished in September 2011 for patients over 18 years old and suffering of rhumatologic illnesses. Results: A total of 49 patients answered the questionnaire (57% women, 43% men), mean age 52.7 years CI95% [49.1; 56.4]. According to these questionnaires, the leaflets helped the patients to better understand: their illness (81.3% of the respondents), the principle of treatment (93.9%), the possible side effects (95.9%) and to cope with them (91.7%). The additional interview was also beneficial for the general comprehension (98.0%) and for the medicine take (95.9%). These results were even higher among the recent patients who have been treated with Biologics for less than a year. Information provided in the leaflet was evaluated as 7.9/10, whereas information provided by the interview was evaluated as 8.5/10. Some patients expressed the need in extra information on a leaflet (14%), particularly about the mechanism of action of the medicine. 27% of the respondents were in favor of a second interview with a pharmacy student in the future. Conclusions: Patients gained advantage from therapeutic information on biologics and pharmacist action was recognized and benificial. This leads us to believe that a long-term application and a larger sample could provide better results. This study confirms that many rheumatologic patients treated with Biologics need better therapeutic information on their treatment and its potential side effects. This study also allows to screen patients needing or demanding therapeutic education. Pha-BRIC study continues with an observation of patients knowledge evolution before and after pharmacist intervention. References: B. Combe et al. EULAR recommendations for the management of early arthritis (ESCISIT) Ann Rheum Dis. 2007 January; 66(1): 34–45. Disclosure of Interest: None Declared